1998
DOI: 10.1200/jco.1998.16.8.2803
|View full text |Cite
|
Sign up to set email alerts
|

Autologous stem-cell transplantation for non-Hodgkin's lymphomas: the role of graft purging and radiotherapy posttransplantation--results of a retrospective analysis on 120 patients autografted in a single institution.

Abstract: This retrospective analysis suggests that marrow purging and posttransplant radiotherapy improve the outcome of patients with NHL autografted in first remission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 35 publications
1
33
0
Order By: Relevance
“…2 Although no completed randomised trial has examined the impact of IFRT added to HDT and AuSCT, several retrospective series have indicated improved outcomes with this strategy. [3][4][5][6][7][8][9][10][11] Important concerns regarding the use of IFRT are its potential toxicity and the logistical constraints in integrating radiotherapy with the overall transplant programme. 12 Two notable forms of toxicity are pneumonitis and haematological toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 Although no completed randomised trial has examined the impact of IFRT added to HDT and AuSCT, several retrospective series have indicated improved outcomes with this strategy. [3][4][5][6][7][8][9][10][11] Important concerns regarding the use of IFRT are its potential toxicity and the logistical constraints in integrating radiotherapy with the overall transplant programme. 12 Two notable forms of toxicity are pneumonitis and haematological toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8]11 In two studies, the improvement in progressionfree survival associated with the use of IFRT was significant on multivariate analysis. 9,10 Furthermore, in a recent report from the US Autologous Blood and Marrow Transplant Registry, multivariate analysis demonstrated that patients who received radiotherapy experienced a reduced relative risk of death. 11 Nonetheless, the optimal method and timing of IFRT with AuSCT remains to be defined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro purging with anti-B cell monoclonal antibodies typically results in a 2-3 log depletion of tumour cells, 8,9 while treatment of the graft with chemotherapeutic agents such as mafosfamide has resulted in a similar level of depletion. 10 Other techniques have employed positive selection of CD34 + cells with antibodies conjugated to magnetic beads. 11 However, while all of these techniques can reduce the level of tumour cell contamination, the majority of grafts remain PCR positive.…”
Section: In Vitro Purgingmentioning
confidence: 99%
“…This is further reflected in the disappointing outcomes experienced with in vitro purged ASCT: studies conducted to date have not been translated in any significant increased survival in patients receiving purged compared with unpurged stem cell grafts. 10,12,13 In vitro purging methods are also invariably associated with substantial cell losses, and are frequently expensive to perform. 14 …”
Section: In Vitro Purgingmentioning
confidence: 99%